Fructose content and composition of commercial HFCS-sweetened carbonated beverages - White, J S; Hobbs, L J; Fernandez, S (International Journal of Obesity, 2015)
Objective: The obesigenic and related health effects of caloric sweeteners are subjects of much current research. Consumers can properly adjust their diets to conform to nutritional recommendations only if the sugars composition of foods and beverages is accurately measured and reported, a matter of recent concern. We tested the hypothesis that high-fructose corn syrup (HFCS) used in commercial carbonated beverages conforms to commonly assumed fructose percentages and industry technical specifications, and fulfills beverage product label regulations and Food Chemicals Codex-stipulated standards. Design: A high-pressure liquid chromatography method was developed and verified for analysis of sugars in carbonated beverages sweetened with HFCS-55. The method was used to measure percent fructose in three carbonated beverage categories. Method verification was demonstrated by acceptable linearity ( R 2 >0.99), accuracy (94–104% recovery) and precision (RSD<2%). Result: Fructose comprised 55.58% of total sugars (95% confidence interval 55.51–55.65%), based on 160 total measurements by 2 independent laboratories of 80 randomly selected carbonated beverages sweetened with HFCS-55. The difference in fructose measurements between laboratories was significant but small (0.1%), and lacked relevance. Differences in fructose by product category or by product age were not statistically significant. Total sugars content of carbonated beverages showed close agreement within product categories (95% confidence interval=0.01–0.54%). Conclusions: Using verified analytical methodology for HFCS-sweetened carbonated beverages, this study confirmed the hypothesis that fructose as a percentage of total sugars is in close agreement with published specifications in industry technical data sheets, published literature values and governmental standards and requirements. Furthermore, total sugars content of commercial beverages is consistent with common industry practices for canned and bottled products and met the US Federal requirements for nutritional labeling and nutrient claims. Prior concerns about composition were likely owing to use of improper and unverified methodology.